Os sentidos da relação educação e saúde e o trabalho pedagógico no âmbito hospitalar: contribuições da epistemologia da prática à formação docente - Moreno, Lêda Virgínia Alves (2012)
This research aims at investigating the influence of the meaning attributed by teacher educators, working in hospital premises, to the relationship between Health and Education, so as to understand the building blocks of their teaching practice, and their understanding of concepts such as quality of life , human dignity and citizenship , in the context of the pedagogical work they carry out with students who are, temporarily or permanently, hospitalized. The context of this investigation was the Oncology Pediatric Ward of a private hospital in the city of São Paulo. The methodological approach was initially based on bibliographical and documentation research and was later complemented by the qualitative survey which sprung from the case study. The participants in this research were teacher educators who have been teaching hospitalized school students for more than 10 years. In the light of literature, testimonials given by the teacher educators and the documentation researched, three main co-related areas have been appointed: the field of epistemology of practice, the training of teacher educators, and the context in which teacher educators build their practice within the hospital premises. The current research project has enabled us to identify, as a conclusive result, the urgent need for creating new paradigms regarding the connection between Education and Health Care, as well as the practices in the teacher education courses, both at undergraduate and graduate levels. Another important need that emerged from this research is that the work carried out by teacher educators in hospital premises must be guided by values of authenticity and quality interpersonal skills. This presupposes that the development of meaningful learning is intimately connected to the level of awareness of the experiences lived and shared by the participants in the process. This approach enables the teacher educators to move away from traditional restrictive and uncritical models. The search for new paradigms towards the restructuring of the pedagogical work in the hospital also enabled us to observe how the connection between the meaning attributed to the relationship between Health and Education, by teacher educators, is directly connected to their understanding of concepts such as quality of life , autonomy and citizenship , and thence the need for clear concepts in the field of epistemology of practice, in order to shape the development of integrative practices that can guarantee to the hospitalized student his or her unalienable right: the dignity of human life